Targeting metabolic abnormalities to reverse fibrosis in iatrogenic laryngotracheal stenosis. (20th September 2017) - Murphy, Michael K.; Motz, Kevin M; Ding, Dacheng; Yin, Linda; Duvvuri, Madhavi; Feeley, Michael; Hillel, Alexander T.
Abstract : Objective: Management of laryngotracheal stenosis (LTS) remains primarily surgical, with a critical need to identify targets for adjuvant therapy. Laryngotracheal stenosis scar fibroblasts exhibit a profibrotic phenotype with distinct metabolic shifts, including an increased glycolysis/oxidative phosphorylation ratio. This study examines the effects of the glutamine antagonist 6‐diazo‐5‐oxo‐l‐norleucine (DON) on collagen production, gene expression, proliferation, and metabolism of human LTS‐derived fibroblasts in vitro. Method: Paired normal and scar‐derived fibroblasts isolated from subglottic and proximal tracheal tissue in patients with iatrogenic laryngotracheal stenosis (iLTS) were cultured. Proliferation rate, gene expression, protein production, and cellular metabolism were assessed in two conditions: 1) fibroblast growth medium, and 2) fibroblast growth medium with 1 × 10 −4 M DON. Results: DON treatment reduced cellular proliferation rate ( n = 7, P = 0.0150). Expression of genes collagen 1 and collagen 3 both were reduced ( n = 7, P = 0.0102, 0.0143, respectively). Soluble collagen production decreased ( n = 7, P = 0.0056). As measured by the rate of extracellular acidification, glycolysis and glycolytic capacity decreased ( n = 7, P = 0.0082, 0.0003, respectively). adenosine triphosphate (ATP) production and basal respiration decreased ( n = 7, P = 0.0045, 0.0258, respectively), determined by measuring the cellular rate of oxygen consumption. Conclusion: The glutamine antagonist DON reverses profibrotic changes by inhibiting both glycolysis and oxidative phosphorylation in iLTS scar fibroblasts. In contrast to untreated iLTS scar fibroblasts, collagen gene expression, protein production, metabolic rate, and proliferation were significantly reduced. These results suggest DON and/or its derivatives as strong candidates for adjuvant therapy in the management of iatrogenic laryngotracheal stenosis. Enzymes involved in glutamine metabolism inhibited by DON offer targets for future investigation. Level of Evidence: NA. Laryngoscope, 128:E59–E67, 2018